PENERAPAN MODIFIKASI JAWS BALL TERHADAP MINAT SISWA DALAM PERMAINAN BOLA VOLI KELAS VII SMPN 2 CIKAMPEK - Rifqi Muhamad Aziz; Rhama Nurwansyah Sumarno; Aria Kusuma Yuda Ryanto; Irfan Zinat Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is a quantitative research. The purpose of this study was to determine the extent of the application of interest in volleyball games in grade VII students at SMPN 2 Cikampek. This study uses a quantitative approach with a questionnaire research method. This research was conducted at SMAN 1 Lemahabang. The population of this study was 45 members/participants as samples. The sampling technique used in this study was systematic sampling. The form of research design used pre-experimental design with a one-group pretest-posttest design. The function of the research instrument is to obtain the data needed when researchers are collecting information in the field. Making instruments in quantitative research is part of the researcher's activities entering the field, especially in the use of questionnaires from this study, the average before treatment and after treatment experienced a significant increase, namely the mean pretest 126.09 to the mean posttest 136.16. Meanwhile, the results of the calculation of the Paired Sample T Test hypothesis test with the data obtained from this study are the significance value (2-tailed) 0.000 <0.05, meaning that there is a significant application between the average value before treatment and the average value after treatment. It can be concluded that the modification of the jaws ball can have an effect on the volleyball game towards the interest of class VII students of SMPN 2 Cikampek.